MODEL MATEMATIS MONOD TYPE KINETIC UNTUK MENGANALISIS PRODUKTIVITAS BIOGAS PADA BIOREAKTOR LIMBAH RUMAH TANGGA - Rahma Miyati; Riri Syafitri Lubis; Dedy Juliandri Panjaitan (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2026)
Biogas is gas produced from biochemical processes in the form of biomass decomposition which can be used as an energy source. Biogas has great opportunities for development. Input materials for biogas production are centralized and their availability is guaranteed continuously because they are easy to obtain. The alternative experimental design in this research using a kinetic type monod is expected to be able to find the optimal input path. The Monod Type Kinetic model involves a logistic growth model. From the model results, the process of determining fixed points is carried out, analyzing the stability of each fixed point and carrying out numerical simulations at one of the fixed points. The simulation aims to show that the model has stability in the form of stable nodes and stable spirals. The aim of this research is to determine biogas productivity in household waste bioreactors and to implement a monod type kinetic mathematical model on biogas productivity in household waste bioreactors. The results of this research show that biogas productivity in household waste bioreactors in the last two months in Medan City resulted in microbial growth (fg/h) in the bioreactor space following a polynomial equation with a level of agreement between variables R2 of 0.3128. The implementation of the monod type kinetic mathematical model on biogas productivity in household waste bioreactors in the city of Medan was carried out by calculating the microbial growth rate based on biogas productivity and then determining the growth rate based on simulation, thereby providing a microbial growth rate model so that microbial growth rates could be seen.